Identification of a New Peptide for Fibrosarcoma Tumor Targeting and Imaging In Vivo. (5th December 2010) - Wu, Chia-Che; Lin, Erh-Hsuan; Lee, Yu-Ching; Tai, Cheng-Jeng; Kuo, Tsu-Hsiang; Wang, Hsin-Ell; Luo, Tsai-Yueh; Fu, Ying-Kai; Chen, Haw-Jan; Sun, Ming-Ding; Wu, Chih-Hsiung; WU, Cheng-Wen; et al.
Abstract : A 12-mer amino acid peptide SATTHYRLQAAN, denominated TK4, was isolated from a phage-display library with fibrosarcoma tumor-binding activity. In vivo biodistribution analysis of TK4-displaying phage showed a significant increased phage titer in implanted tumor up to 10-fold in comparison with normal tissues after systemic administration in mouse. Competition assay confirmed that the binding of TK4-phage to tumor cells depends on the TK4 peptide. Intravenous injection of 131 I-labeled synthetic TK4 peptide in mice showed a tumor retention of 3.3% and 2.7% ID/g at 1- and 4-hour postinjection, respectively. Tumor-to-muscle ratio was 1.1, 5.7, and 3.2 at 1-, 4-, and 24-hour, respectively, and tumors were imaged on a digital γ-camera at 4-hour postinjection. The present data suggest that TK4 holds promise as a lead structure for tumor targeting, and it could be further applied in the development of diagnostic or therapeutic agent.